Laminated nonwoven fabric and absorbent article comprising same
Patent Information
- Application Number
- JP2021049728
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-03-24
Smart Images

Figure 0007651336000008 
Figure 0007651336000009 
Figure 0007651336000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated nonwoven fabric and an absorbent article including the same. [Background technology]
[0002] Absorbent articles such as sanitary napkins generally include an absorbent body that is the main liquid absorbing portion, and a fiber sheet such as a top sheet, etc. From the viewpoint of suppressing liquid residue in the fiber sheet and improving the wearing comfort of the absorbent article, a technique of applying a fiber treatment agent to the fiber sheet included in the absorbent article is known. For example, Patent Document 1 discloses a sheet to which a water permeability agent is applied, the water permeability agent comprising predetermined contents of a cationized (poly)amine (a), an ester (b), a dialkyl sulfosuccinate salt (c), an alkyl phosphate salt (d), at least one glycine derivative (e) selected from trialkylglycine derivatives and (alkylamide group-containing alkyl)dialkylglycine derivatives, and a polyoxyalkylene-modified silicone (f).
[0003] The applicant has also previously proposed a nonwoven fabric in which multiple fiber layers are integrated at multiple joints, in which the fiber layer on one side of the nonwoven fabric contains helically crimped fibers and non-helical fibers, and the fiber layer on the other side has convex portions containing a liquid membrane cleaving agent (Patent Document 2).
[0004] In addition, apart from the technical field of absorbent articles, the present applicant has previously proposed a hydrophilic treatment agent composition containing an internal olefin sulfonate, a polyvalent metal ion, and water, in which the molar ratio of the internal olefin sulfonate and the polyvalent metal ion is within a predetermined range, as a hydrophilic treatment agent intended for various solid surfaces such as hard surfaces, fabric surfaces, skin surfaces, and hair surfaces (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-247128 A [Patent Document 2] JP 2019-002099 A [Patent Document 3] JP 2020-125451 A Summary of the Invention [Problem to be solved by the invention]
[0006] From the viewpoint of obtaining a good wearing comfort, absorbent articles such as sanitary napkins are required to have a good dryness even after absorbing liquids such as menstrual blood. Patent Documents 1 and 2 have room for improvement in the effect of suppressing liquid residue on the nonwoven fabric surface. The hydrophilic treatment composition described in Patent Document 3 exhibits excellent hydrophilicity for various solid surfaces such as hard surfaces. However, the document does not disclose any study on whether the hydrophilic treatment composition is useful for various performances of absorbent articles when used as a component of the absorbent article.
[0007] Therefore, an object of the present invention is to provide a laminated nonwoven fabric which is excellent in dryness by suppressing liquid residue on the surface. [Means for solving the problem]
[0008] The present invention relates to a laminated nonwoven fabric having at least two layers: a first fibrous layer and a second fibrous layer laminated thereon. The second fibrous layer preferably has a bulk density higher than that of the first fibrous layer. The second fiber layer preferably contains the following compound A and compound B. Compound A: Hydroxyalkanesulfonic acid salt having 12 to 22 carbon atoms Compound B: Internal olefin sulfonate having 12 to 22 carbon atoms Effect of the Invention
[0009] According to the laminated nonwoven fabric of the present invention, liquid residue on the surface of the nonwoven fabric is suppressed, and the nonwoven fabric has excellent dryness. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is an enlarged cross-sectional view showing one embodiment of the laminated nonwoven fabric according to the present invention. [Diagram 2] FIG. 2 is a perspective view showing another embodiment of the laminated nonwoven fabric according to the present invention. [Diagram 3] FIG. 3(a) is a perspective view showing still another embodiment of the laminated nonwoven fabric according to the present invention, and FIG. 3(b) is a cross-sectional view of the laminated nonwoven fabric. [Figure 4] FIG. 4 is a perspective view showing still another embodiment of the laminated nonwoven fabric according to the present invention. [Diagram 5] FIG. 5(a) is a perspective view showing still another embodiment of the laminated nonwoven fabric according to the present invention, and FIG. 5(b) is a cross-sectional view of the laminated nonwoven fabric. [Figure 6] FIG. 6(a) is a perspective view showing still another embodiment of the laminated nonwoven fabric according to the present invention, and FIG. 6(b) is a cross-sectional view of a protruding portion of the laminated nonwoven fabric. [Figure 7] FIG. 7(a) is a perspective view showing still another embodiment of the laminated nonwoven fabric according to the present invention, and FIG. 7(b) is a cross-sectional view of the laminated nonwoven fabric. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the laminated nonwoven fabric of the present invention will be described based on its preferred embodiments with reference to the drawings. FIG. 1 shows one embodiment of the laminated nonwoven fabric of the present invention. The laminated nonwoven fabric 10 shown in FIG. 1 has a first fiber layer 11 and a second fiber layer 12 laminated thereon. The first fiber layer 11 and the second fiber layer 12 are disposed adjacent to each other. The laminated nonwoven fabric 10 of this embodiment has a two-layer structure consisting of the first fiber layer 11 and the second fiber layer 12, but the laminated nonwoven fabric of the present invention only needs to have at least two layers, and may have a laminated structure of three or more layers. The laminated nonwoven fabric 10 of this embodiment has a first side F1 and a second side F2 located on the opposite side. The first side F1 and the second side F2 are each perpendicular to the thickness direction Z of the laminated nonwoven fabric 10. The first fiber layer 11 forms the first side F1 of the nonwoven fabric 10, and the second fiber layer 12 forms the second side F2 of the nonwoven fabric 10.
[0012] The laminated nonwoven fabric 10 of this embodiment has a plurality of joints 13 where the first fiber layer 11 and the second fiber layer 12 are integrated. That is, the first fiber layer 11 and the second fiber layer 12 are partially joined by the plurality of joints 13. The joints 13 can be formed by an embossing method with or without heat, an ultrasonic embossing method, or the like. When the joints 13 are formed by such an embossing method, the joints 13 become parts where the constituent fibers of the laminated nonwoven fabric 10 are denser than other parts. The joints 13 may be formed by adhesion using an adhesive instead of embossing.
[0013] The shape of the joint 13 in a plan view is not particularly limited, and may be a circle, an ellipse, a triangle, a rectangle, or a combination of these, or may be formed in a linear shape such as a straight line or a curved line. From the viewpoint of further improving the dryness described below, the joints 13 are preferably arranged in a scattered manner in the planar direction.
[0014] The joints 13 in this embodiment are formed by embossing, and the constituent fibers of the laminated nonwoven fabric 10 are thinner and denser than other portions. The joints 13 in this embodiment are recessed relatively to the first surface F1 side of the laminated nonwoven fabric 10 compared to other portions, and the other portions protrude toward the first surface F1 side beyond the joints 13. As a result, the laminated nonwoven fabric 10 has unevenness on the first surface F1 side. That is, the laminated nonwoven fabric 10 has a plurality of protruding portions 14 protruding toward the first surface F1 side and a plurality of recessed portions 15 recessed toward the second surface F2 side. The laminated nonwoven fabric 10 of this embodiment has irregularities on the first surface F1 side, while the second surface F2 side is flat. As described below, the laminated nonwoven fabric 10 may have irregularities on the second surface F2 side, but from the viewpoint of further improving dryness, it is preferable that the laminated nonwoven fabric 10 has irregularities at least on the first surface F1 side.
[0015] The protrusions 14 in this embodiment have a solid structure filled with the constituent fibers of the first fiber layer 11 and the second fiber layer 12. From the viewpoint of further improving the feel against the skin due to the unevenness of the laminated nonwoven fabric 10, the maximum thickness H1 (see FIG. 1) of the protrusions 14 is preferably at least 2 times, more preferably at least 20 times, and preferably at most 80 times, more preferably at most 60 times the thickness H2 (see FIG. 1) of the recesses 15. The maximum thickness H1 of the protrusions 14 is the maximum thickness of the laminated nonwoven fabric 10. The thickness H2 of the recesses 15 is the thickness at the joints 13 when observing a cross section of the laminated nonwoven fabric 10. In this embodiment, the joints 13 are portions whose both surfaces are flat (see FIG. 1).
[0016] The thickness of each part of the laminated nonwoven fabric 10 is measured by the following method. First, a piece of 60 mm x 60 mm is cut out from the laminated nonwoven fabric 10, and this is used as a sample piece. Next, a metal plate with a diameter of 56 mm and a perfect circle shape is placed on the sample stage of a laser displacement meter (Keyence Corporation, CCD laser displacement sensor LK-085) under conditions of a temperature of 20 ± 2 ° C. and a relative humidity of 65 ± 5%. This metal plate can apply a load of 50 Pa to the sample piece. Next, the laser irradiation point is aligned with the center position of the upper surface of the metal plate, and a reference point P0, which is the height position of the metal plate, is measured. Next, the metal plate on the sample stage is temporarily removed, and the sample piece is placed on the sample stage with the second surface F2 side facing down. Next, the metal plate is placed on the sample piece so that the entire area of the sample piece overlaps. In this way, with a load of 50 Pa applied to the sample piece, the laser irradiation point is aligned with the center position of the upper surface of the metal plate, and a measurement point P1, which is the height position of the metal plate, is measured. Then, the difference between the reference point P0 and the measurement point P1 is calculated and this is defined as the maximum thickness H1 of the protrusion 14.
[0017] When measuring the thickness H2 of the recess 15, the cut surface of the laminated nonwoven fabric 10 cut so as to pass through the center of the joint 13 is magnified and observed in the same manner as in "Measurement of bulk density in a fiber layer" described below. That is, the thickness of the joint 13 in the observation field of the cut surface is measured. If the joint 13 is inclined obliquely with respect to the horizontal plane (sample stage) or if the joint 13 is curved, the part where no constituent fibers are present and located below the inclined or curved part is not included in the thickness of the joint 13. The above measurements are carried out at any six points on the laminated nonwoven fabric 10, and the average value of these measurements is taken as the thickness H2 of the joint 13.
[0018] The area ratio of the joints 13 in the laminated nonwoven fabric 10 is preferably 5% or more, more preferably 7% or more, and is preferably 30% or less, more preferably 20% or less, and is preferably 5% or more and 30% or less, more preferably 7% or more and 20% or less. With this configuration, liquid residue in the laminated nonwoven fabric 10 can be further suppressed.
[0019] The area ratio of the bonded portions 13 is determined by the following measurement method. A sample piece measuring 20 mm x 20 mm is cut out from the laminated nonwoven fabric 10. A planar photograph of the sample piece is obtained using a microscope (VHX-6000, manufactured by Keyence Corporation) under conditions of a temperature of 20±2°C and a relative humidity of 65±5%. The number of bonded portions 13 included in the range of 20 mm x 20 mm of the sample piece is counted from the planar photograph, and the area per unit when viewed in plan is measured. The total area of the bonded portions 13 in the sample piece is then determined by multiplying the area by the number of bonded portions 13. The total area of the bonded portions 13 is then calculated by dividing the total area of the bonded portions 13 by the measured area of 400 mm of the sample piece. 2 The ratio (%) of (total area of bonded portions 13 / measured area of sample piece) divided by is calculated. The above measurements are performed for five sample pieces, and the average value is taken as the area ratio (%) of bonded portions 13.
[0020] Each of the first fiber layer 11 and the second fiber layer 12 is composed of an aggregate of fibers. The second fiber layer 12 has a bulk density higher than that of the first fiber layer 11. This provides a fiber density gradient to the laminated nonwoven fabric 10, thereby improving the liquid absorption properties. In order to further improve such effects, the bulk density of each of the first fiber layer 11 and the second fiber layer 12 is preferably within the following ranges. The ratio of the bulk density of the first fiber layer 11 to the bulk density of the second fiber layer 12 (bulk density in the first fiber layer 11 / bulk density in the second fiber layer 12) is preferably 0.30 or more, more preferably 0.40 or more, and is preferably 0.90 or less, more preferably 0.80, and is preferably 0.30 or more and 0.90 or less, more preferably 0.40 or more and 0.80 or less. The bulk density of the first fiber layer 11 is preferably 0.01 g / cm 3 More preferably, 0.015 g / cm 3 or more, and preferably 0.06 g / cm 3 Less than or equal to 0.05 g / cm 3 or less, and preferably 0.01 g / cm 3 More than 0.06g / cm 3 Less than or equal to 0.015 g / cm 3 More than 0.05g / cm 3 The following is the result. The bulk density of the second fiber layer 12 is preferably 0.02 g / cm 3 More preferably, 0.03 g / cm 3 More preferably, it is 0.08 g / cm 3 Less than or equal to 0.07 g / cm 3 or less, and preferably 0.02 g / cm 3 More than 0.08g / cm 3 Less than or equal to 0.03 g / cm 3 or more and less than 0.07.
[0021] [Measurement of bulk density in fiber layer] The bulk density of each fiber layer of the first fiber layer 11 and the second fiber layer 12 is measured by the following method. First, the cut surface of the laminated nonwoven fabric 10 is observed as follows using a microscope (VHX-6000, manufactured by Keyence Corporation) under conditions of a temperature of 20±2°C and a relative humidity of 65±5%. When the laminated nonwoven fabric 10 has projections and recesses, the laminated nonwoven fabric 10 is cut so as to pass through the apex of the projection 14 having the maximum thickness H1 of the laminated nonwoven fabric 10, and the laminated nonwoven fabric 10 is placed on a sample stage of the microscope with the second surface F2 side of the laminated nonwoven fabric 10 facing down. The observation is performed in a state where a square glass substrate is placed on the laminated nonwoven fabric 10 so that a pressure of 50 Pa is applied to the nonwoven fabric. That is, the cut surface of the laminated nonwoven fabric 10 under a load of 50 Pa is magnified and observed using a microscope. The magnification during observation is adjusted to a magnification (50 to 100 times) where the thickness of the entire nonwoven fabric fits within the screen. The interface between the first fiber layer 11 and the second fiber layer 12 during observation was defined as the boundary between two regions with different fiber diameters and fiber shapes, and the height between the glass substrate surface and said interface was defined as the thickness [mm] of the first fiber layer 11, and the height between the sample table surface and said interface was defined as the thickness [mm] of the second fiber layer 12. Next, a portion other than the joints 13 is carefully cut out from the laminated nonwoven fabric 10 to be measured using precision scissors, and its area is measured. This cut-out portion is further separated into the first fiber layer 11 and the second fiber layer 12, and the mass [g] of each is measured. The measured mass of each fiber layer 11, 12 is divided by the area of the cut-out portion to obtain the basis weight [g / m2] of the first fiber layer 11. 2 ] and the basis weight [g / m 2 ] is required. The basis weight [g / m 2 ] by the thickness [mm] of the fiber layer corresponding to that basis weight to obtain the bulk density [g / cm 3 ] is calculated. The above measurements are carried out at any six points on the laminated nonwoven fabric 10, and the average of these measurements is taken as the bulk density of the fiber layer.
[0022] From the viewpoint of further improving the bonding between the first fiber layer 11 and the second fiber layer 12, the first fiber layer 11 preferably contains heat-fusible fibers. Heat-fusible fibers are fibers that fuse to each other by the action of heat, and are made from thermoplastic resin. Examples of thermoplastic resins include polyolefins such as polyethylene (PE) and polypropylene (PP); polyesters such as polyethylene terephthalate (PET); polyamides such as nylon 6 and nylon 66; polyacrylic acid, polymethacrylic acid alkyl esters, polyvinyl chloride, polyvinylidene chloride, and the like, and these may be used alone or in combination of two or more. Also, as the heat-fusible fiber, a composite fiber consisting of two or more components, a low melting point component and a high melting point component, may be used. As such a composite fiber, a core-sheath type composite fiber or a side-by-side type composite fiber may be used. Furthermore, as the core-sheath type composite fiber, for example, a core made of high melting point PET or PP and a sheath made of low melting point PET, PP, or PE may be used. The core-sheath type composite fiber may be a concentric type or an eccentric type.
[0023] From the viewpoint of making it easier to form the joint 13 by embossing, the content of the heat-fusible fibers in the first fiber layer 11 is preferably 50 mass% or more, more preferably 80 mass% or more, and preferably 100 mass% or less, and is preferably 50 mass% or more and 100 mass% or less, more preferably 80 mass% or more and 100 mass% or less, relative to the total mass of the first fiber layer 11. The first fiber layer 11 may be composed of one type of fiber, or may be composed of two or more types of fiber.
[0024] From the viewpoint of facilitating the formation of irregularities in the laminated nonwoven fabric 10, when the second fiber layer 12 contains a heat-shrinkable fiber as described below, the first fiber layer 11 preferably contains a non-heat-shrinkable fiber, and more preferably is made of a non-heat-shrinkable fiber. Non-heat-shrinkable fibers include both fibers that do not exhibit heat shrinkability and fibers that do not substantially shrink at the heat-shrinkage initiation temperature of the heat-shrinkage fiber contained in the second fiber layer 12 described below.
[0025] The second fiber layer 12 of the present embodiment contains heat-shrinkable fibers. The heat-shrinkable fibers are fibers that have heat-shrinkability and shrink when heat is applied. Although such heat-shrinkable fibers have been heat-shrunk by a heating treatment, they still have heat-shrinkability. As the heat-shrinkable fibers, those made of the above-mentioned thermoplastic resin and having heat-shrinkability are preferably used. By including a non-heat-shrinkable fiber in the first fiber layer 11 and a heat-shrinkable fiber in the second fiber layer 12, it is possible to easily form projections and recesses in the first fiber layer 11 of the laminated nonwoven fabric 10 by heat treatment. A method for producing the laminated nonwoven fabric 10 will be described later.
[0026] The second fiber layer 12 of this embodiment contains a helical crimped fiber as a heat-shrinkable fiber. More specifically, it contains a latently crimped fiber. The latently crimped fiber can be handled in the same manner as a conventional fiber for nonwoven fabric before being heated, and has the property of developing a helical crimp and shrinking when heated at a predetermined temperature. The latently crimped fiber is, for example, an eccentric core-sheath type or side-by-side type composite fiber made of two types of thermoplastic polymer materials with different shrinkage rates. Examples of such fibers include those described in JP-A-9-296325 and JP-A-2759331.
[0027] From the viewpoint of making it easier to form unevenness in the laminated nonwoven fabric 10, the content of heat-shrinkable fibers in the second fiber layer 12 is preferably 50 mass% or more, more preferably 80 mass% or more, and preferably 100 mass% or less, relative to the total mass of the second fiber layer 12, and is also preferably 50 mass% or more and 100 mass% or less, more preferably 80 mass% or more and 100 mass% or less. The second fiber layer 12 may be composed of one type of fiber, or may be composed of two or more types of fibers.
[0028] Furthermore, from the viewpoint of making it easier to form irregularities in the laminated nonwoven fabric 10, the first fiber layer 11 may contain a heat-extensible fiber and the second fiber layer 12 may contain a non-heat-extensible fiber. That is, it is preferable that the first fiber layer 11 contains a heat-extensible fiber and the second fiber layer 12 contains a non-heat-extensible fiber, and it is more preferable that the first fiber layer 11 is made of a heat-extensible fiber and the second fiber layer 12 is made of a non-heat-extensible fiber.
[0029] A heat-extensible fiber is a fiber whose length is extended by heating, and is a fiber that is extended at a temperature of 90° C. or more, preferably 110° C. to 140° C. Heat-extensible fibers are extended by heat treatment, and as a result, the fiber space is larger than that of non-extensible fibers. Examples of such fibers include fibers that are extended by heating due to a change in the crystal state of the resin, and fibers that have been subjected to a crimping process and whose apparent length is extended by releasing the crimp. Non-thermally extensible fibers are fibers that do not substantially expand in length upon application of heat. Examples of the thermally extensible fibers and non-thermally extensible fibers that can be used include those described in paragraphs
[0013] and
[0037] to
[0040] of JP 2005-350836 A and those described in paragraphs
[0012] and
[0024] to
[0046] of JP 2011-127258 A.
[0030] From the viewpoint of further improving the liquid drawability due to the density gradient described above, it is preferable that the fineness of the constituent fibers of the second fiber layer 12 is smaller than that of the first fiber layer 11. From the same viewpoint as above, it is preferable that the fineness of the constituent fibers of each of the first fiber layer 11 and the second fiber layer 12 is within the following range. The ratio of the fineness of the constituent fibers of the first fiber layer 11 to the fineness of the constituent fibers of the second fiber layer 12 (fineness of the constituent fibers of the first fiber layer 11 / fineness of the constituent fibers of the second fiber layer 12) is preferably 1.01 or more, more preferably 1.03 or more, and is preferably 8.00 or less, more preferably 5.00 or less, and is preferably 1.01 or more and 8.00 or less, more preferably 1.03 or more and 5.00 or less. The fineness of the constituent fibers of the first fiber layer 11 is preferably 1.0 dtex or more, more preferably 1.5 dtex or more, and is preferably 8.0 dtex or less, more preferably 5.0 dtex or less, and is preferably 1.0 dtex or more and 8.0 dtex or less, more preferably 1.5 dtex or more and 5.0 dtex or less. The fineness of the constituent fibers of the second fiber layer 12 is preferably 0.5 dtex or more, more preferably 1.0 dtex or more, and is preferably 5.0 dtex or less, more preferably 4.0 dtex or less, and is preferably 0.5 dtex or more and 5.0 dtex or less, more preferably 1.0 dtex or more and 4.0 dtex or less.
[0031] The fiber fineness can be measured by the following method. 2 ) to prepare a measurement sample. Next, the measurement sample is viewed in cross section, and the fiber thicknesses of 10 standard fibers at positions spaced 0.05 mm apart from the first surface F1 of the measurement sample in the thickness direction are measured using an electron microscope, and the average fiber thickness Dn (μm) is calculated. Next, the constituent resins of the standard fibers at positions spaced 0.05 mm apart from the first surface F1 of the measurement sample in the thickness direction are identified, and a differential scanning calorimeter (DSC) is used to determine the theoretical fiber presence density Pn (g / cm 3 The average fiber thickness Dn (μm) and theoretical fiber density Pn (g / cm 3 ) is used to calculate the weight (g) per 10,000 m of fiber length, and this calculated value is regarded as the fineness (dtex) of the constituent fibers of the first fiber layer 11. The fineness of the constituent fibers of the second fiber layer 12 is determined by the standard fiber thickness of the second surface F2 and the theoretical fiber density Pn (g / cm 3 ) can be obtained in the same manner as in the fineness of the constituent fibers of the first surface F1.
[0032] From the viewpoint of forming convex portions on the first surface side of the first fiber layer and allowing body fluids to pass therethrough more efficiently, the basis weight of the laminated nonwoven fabric 10 is preferably 10 g / m 2 More preferably, 20 g / m2 More preferably, it is 120 g / m 2 Less than 100 g / m 2 and preferably 10 g / m 2 More than 120g / m 2 Less than 20 g / m 2 More than 100g / m 2 The following is the result. In order to further suppress liquid residue in the first fiber layer, the basis weight of the first fiber layer 11 is preferably 5 g / m 2 More preferably, 10 g / m 2 More preferably, it is 60 g / m 2 Less than 50 g / m 2 and preferably 5 g / m 2 More than 60g / m 2 Less than 10 g / m 2 More than 50g / m 2 The following is the result. From the viewpoint of efficiently transferring body fluids to the second fiber layer side and further suppressing the liquid remaining in the first fiber layer, the basis weight of the second fiber layer 12 is preferably 5 g / m 2 More preferably, 10 g / m 2 More preferably, it is 60 g / m 2 Less than 50 g / m 2 and preferably 5 g / m 2 More than 60g / m 2 Less than 10 g / m 2 More than 50g / m 2 The following is the result.
[0033] In the second fiber layer 12 of the laminated nonwoven fabric 10, the following compounds A and B, which are anionic surfactants, are disposed. Compound A: Hydroxyalkanesulfonic acid salt having 12 to 22 carbon atoms Compound B: Internal olefin sulfonate having 12 to 22 carbon atoms By disposing compound A and compound B in the second fiber layer 12, a hydrophilicity gradient is imparted from the first fiber layer 11 to the second fiber layer 12. This can increase the liquid attraction from the first fiber layer 11 to the second fiber layer 12.
[0034] Compound A and compound B can be produced by the following method. First, β-sultone is quantitatively produced by sulfonating an olefin having a double bond inside the olefin chain (hereinafter referred to as "internal olefin"). A part of this β-sultone is converted into γ-sultone and olefin sulfonic acid, which are further converted into compound A (hydroxyalkanesulfonate) and compound B (internal olefinsulfonate) by neutralization and hydrolysis steps (for example, J. Am. Oil Chem. Soc. 69, 39 (1992)). The hydroxy group of compound A obtained here, i.e., hydroxyalkanesulfonate, is inside the alkane chain. Also, the double bond of compound B, i.e., internal olefinsulfonate, is inside the olefin chain (see formula (2) described later). In other words, "internal olefinsulfonate" means an unsaturated sulfonate having a double bond inside the hydrocarbon group. The internal olefin has a broad meaning including a case where a trace amount of so-called α-olefin, in which the double bond is located at the first position of the carbon chain, is contained.
[0035] From the viewpoint of carbon neutrality, it is preferable that compound A and compound B are obtained using a raw material internal olefin derived from natural fats and oils (hereinafter also referred to as "raw material internal olefin"). For example, after obtaining an aliphatic alcohol having 12 to 22 carbon atoms from natural fats and oils such as palm oil, the aliphatic alcohol is dehydrated in the presence of a solid catalyst such as alumina to obtain a raw material internal olefin having 12 to 22 carbon atoms. Then, the raw material internal olefin is sulfonated, neutralized, and hydrolyzed, and compound A and compound B are isolated from the product to obtain compound A and compound B. The manufacturing method of compound A and compound B (internal olefin sulfonate) and the raw material internal olefin may be those described in JP 2016-183208 A. Examples of the raw material internal olefin include those obtained by dehydrating aliphatic alcohols having 12 to 22 carbon atoms derived from natural fats and oils, and those obtained by decarbonating fatty acids having 14 to 22 carbon atoms derived from natural fats and oils.
[0036] Compound A is a hydroxyalkanesulfonate having a carbon number distribution of 12 or more and 22 or less. Compound A contains a compound represented by the following formula (1). From the viewpoint of further improving the dryness described later, the carbon number of compound A is preferably 14 or more, more preferably 16 or more, and also preferably 20 or less, more preferably 18 or less, and also preferably 14 or more and 20 or less, more preferably 16 or more and 18 or less. In the following formula (1), the total number of carbon atoms in R1 and R2 is 10 or more, preferably 12 or more, more preferably 14 or more, and 20 or less, preferably 18 or less, more preferably 16 or less, and is 10 or more and 20 or less, preferably 12 or more and 18 or less, more preferably 14 or more and 16 or less.
[0037] [ka] In the formula, X represents H, Na, K, Mg, Ca, or ammonium. R1 and R2 each independently represent an alkyl group, and the total number of carbon atoms of both is 10 or more and 20 or less.
[0038] In the formula (1), the alkyl groups represented by R1 and R2 are preferably linear. In the compound represented by formula (1), -SO3X and -OH are each bonded to adjacent carbon atoms, and -SO3X is not located at the end of an alkyl chain, and similarly -OH is not located at the end of an alkyl chain. Compound A includes a plurality of isomers in which the bonding positions of -SO3X and -OH in the alkyl chain are various. Only one of the plurality of isomers may be disposed in the second fiber layer 12, or two or more of the isomers may be disposed.
[0039] In the second fiber layer 12, as the compound A, a hydroxyalkanesulfonate having one type of carbon atom may be disposed, or a hydroxyalkanesulfonate having two or more types of carbon atom may be disposed.
[0040] From the viewpoint of further improving the dryness of the laminated nonwoven fabric 10, it is preferable that the second fiber layer 12 contains, as the compound A, either or both of the following compounds A1 and A2. Compound A1: Hydroxyalkanesulfonate having 16 carbon atoms Compound A2: Hydroxyalkanesulfonate having 18 carbon atoms That is, it is preferable that either compound A1 or compound A2, or both compound A1 and compound A2 are disposed in the second fiber layer 12 as the compound A. From the viewpoint of further improving the dryness of the laminated nonwoven fabric 10 described below, it is more preferable that either compound A1 or compound A2 is disposed in the second fiber layer 12 as the compound A.
[0041] When both compounds A1 and A2 are disposed in the second fiber layer 12 as compound A, from the viewpoints of more efficiently transferring body fluids to the second fiber layer 12 side and further suppressing residual fluid in the first fiber layer 11, the content ratio of compound A1 to compound A2 in the second fiber layer 12 (A1:A2) is preferably 2:1 to 1:2, more preferably 3:2 to 2:3.
[0042] Compound B is an internal olefin sulfonate having a carbon number distribution of 12 or more and 22 or less. Compound B contains a compound represented by the following formula (2). From the viewpoint of further improving the dryness described later, the carbon number of compound B is preferably 14 or more, more preferably 16 or more, and also preferably 20 or less, more preferably 18 or less, also preferably 14 or more and 20 or less, more preferably 16 or more and 18 or less. In the following formula (2), the total number of carbon atoms in R3 and R4 is 9 or more, preferably 11 or more, more preferably 13 or more, and 19 or less, preferably 17 or less, more preferably 15 or less, and is 9 or more and 19 or less, preferably 11 or more and 17 or less, more preferably 13 or more and 15 or less.
[0043] [ka] In the formula, X represents H, Na, K, Mg, Ca, or ammonium. R3 and R4 each independently represent an alkyl group, and the total number of carbon atoms of both is 9 to 19.
[0044] In the formula (2), the alkyl groups represented by R3 and R4 are preferably linear. In the compound represented by formula (2), -SO3X is bonded to adjacent carbon atoms and is not located at the end of the alkyl chain. Compound B includes a plurality of isomers having various bonding positions of -SO3X in the alkyl chain. Only one of the plurality of isomers may be disposed in the second fiber layer 12, or two or more of the isomers may be disposed.
[0045] In the second fiber layer 12, as the compound B, an internal olefin sulfonate having one type of carbon number may be disposed, or an internal olefin sulfonate having two or more types of carbon numbers may be disposed.
[0046] From the viewpoint of further improving the dryness of the laminated nonwoven fabric 10, it is preferable that the second fiber layer 12 contains, as the compound B, either or both of the following compounds B1 and B2. Compound B1: Internal olefin sulfonate having 16 carbon atoms Compound B2: Internal olefin sulfonate having 18 carbon atoms That is, it is preferable that either compound B1 or compound B2, or both compound B1 and compound B2 are disposed in the second fiber layer 12 as compound B. From the viewpoint of further improving the dryness of the laminated nonwoven fabric 10, it is more preferable that either compound B1 or compound B2 is disposed in the second fiber layer 12 as compound B. From the same viewpoint as above, the content ratio of the compound B1 to the compound B2 in the second fiber layer 12 (B1:B2) is preferably 2:1 to 1:2, and more preferably 3:2 to 2:3.
[0047] The second fiber layer 12 contains a compound A and a compound B. The compound A and the compound B may be present in a state of being attached to the surface of the fibers constituting the second fiber layer 12. From the viewpoint of further suppressing liquid residue in the laminated nonwoven fabric 10, the mass ratio (A / B) of compound A to compound B in the second fiber layer 12 is preferably 2.0 or more and 12.0 or less. From the viewpoints similar to those described above, the mass ratio (A / B) in the second fiber layer 12 is more preferably 3.0 or more, further preferably 3.5 or more, even more preferably 4.0 or more, more preferably 10.0 or less, further preferably 8.0 or less, even more preferably 7.0 or less, further preferably 3.0 or more and 10.0 or less, further preferably 3.5 or more and 8.0 or less, even more preferably 4.0 or more and 7.0 or less.
[0048] Each of compound A and compound B has, in its molecule, a lipophilic group (an alkyl chain having 12 to 22 carbon atoms) that is compatible with oil and a hydrophilic group that is compatible with water. Compound A has a hydrophilic group in the middle of the lipophilic group. The inventors have found that when compound A and compound B are arranged in the second fiber layer 12, which has a higher bulk density than the first fiber layer 11, liquid is effectively drawn from the first fiber layer 11 to the second fiber layer 12. In particular, they have found that they exhibit excellent drawing properties for highly viscous liquids such as menstrual blood. This suppresses liquid residue on the first surface F1 of the laminated nonwoven fabric 10, and improves the dryness of the first surface F1. When such a laminated nonwoven fabric 10 is used as a top sheet of an absorbent article such as a napkin, it has excellent dryness even after absorbing liquids such as menstrual blood, and a good wearing feel is obtained.
[0049] The adhesion rate of compound A in the second fiber layer 12, i.e., the ratio of the mass of compound A to the total mass of the second fiber layer 12, is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and also preferably 5.00 mass% or less, more preferably 2.00 mass% or less, and also preferably 0.05 mass% or more and 5.00 mass% or less, more preferably 0.10 mass% or more and 2.00 mass% or less. The total mass of the laminated nonwoven fabric 10 includes the mass of the laminated nonwoven fabric 10 itself as well as the masses of the attached substances such as compound A and compound B. The adhesion rate of compound B in the second fiber layer 12, i.e., the mass ratio of compound B to the total mass of the second fiber layer 12, is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and is also preferably 5.00 mass% or less, more preferably 2.00 mass% or less, and is also preferably 0.01 mass% or more and 5.00 mass% or less, more preferably 0.02 mass% or more and 2.00 mass% or less.
[0050] The adhesion rate of the treatment agent containing compound A and compound B in the second fiber layer 12, i.e., the mass content of the treatment agent relative to the total mass of the second fiber layer 12, is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and also preferably 10.00 mass% or less, more preferably 4.00 mass% or less, and also preferably 0.05 mass% or more and 10.00 mass% or less, more preferably 0.10 mass% or more and 4.00 mass% or less.
[0051] When analyzing the presence or absence, adhesion rate, and content ratio of each compound in a laminated nonwoven fabric 10 in which compound A and compound B, or other compounds described later, are arranged, it is preferable to perform the analysis according to the following procedure. First, the constituent fibers of the layer to be analyzed (the first fiber layer 11 or the second fiber layer 12) are taken out from the laminated nonwoven fabric 10. The constituent fibers of the first fiber layer 11 are taken out from the first surface F1 of the laminated nonwoven fabric 10, and the constituent fibers of the second fiber layer 12 are taken out from the second surface F2. Next, the taken out fibers are washed with an appropriate solvent. Examples of the washing solvent include a mixed solvent of ethanol and methanol, and a mixed solvent of ethanol and water. Next, the solvent (cleaning solvent containing a fiber treatment agent) used to clean the nonwoven fabric to be analyzed is dried, and the residue is quantified to measure the total amount of compounds attached to the nonwoven fabric. In addition, the residue is fractionated by high performance liquid chromatography using appropriate columns and solvents selected according to the constituents, and each fraction is subjected to MS measurement, NMR measurement, elemental analysis, etc., to identify the structure of each fraction. In addition, when the laminated nonwoven fabric 10 contains a polymer compound, the constituent components can be more easily identified by using a method such as gel permeation chromatography (GPC) in combination.
[0052] Compound A and compound B can be analyzed, for example, by the following method. A 50% by volume aqueous ethanol solution and petroleum ether are added to the residue, shaken thoroughly, and allowed to stand, after which the mixture is separated into a petroleum ether phase and an aqueous ethanol phase. The petroleum ether phase is analyzed using gas chromatography under the following conditions, and the amount of internal olefin is quantified from the peak area. The aqueous ethanol phase is analyzed using HPLC-MS under the following conditions, and the hydroxyalkanesulfonate (compound A) and the internal olefinsulfonate (compound B) are separated and quantified.
[0053] Gas chromatography conditions Equipment: Agilent 6850GC (Agilent Technologies) Column: Ultra Alloy UA + -1(HT) Capillary column 15m x 250μm x 0.15μm (Frontier Labs, Inc.) Detector: Flame ionization detector (FID) Injection temperature: 300℃ Detector temperature: 350℃ He flow rate: 3.8mL / min
[0054] ·HPLC-MS conditions Hydroxyalkanesulfonate and internal olefinsulfonate can be separated by HPLC and each can be subjected to MS to identify these compounds. The adhesion rate and the content ratio of each of compound A and compound B can be obtained from the HPLC-MS peak area. HPLC-MS device: Agilent 1100 LC / MSD Model G1946D Mass Spectrometer (Agilent Technologies) Column: L-column ODS (Chemicals Evaluation and Research Institute, Inc., particle size 5 μm, 4.6 × 150 mm) Sample preparation: 1000x dilution with methanol Eluent A: 10 mM ammonium acetate aqueous solution Eluent B: 10 mM ammonium acetate in methanol Gradient conditions: Start (eluent A / eluent B = 30 / 70 (volume ratio)) → 10 min (30 / 70) → 55 min (0 / 100) → 65 min (0 / 100) → 66 min (30 / 70) → 75 min (30 / 70) MS detection: negative ion detection m / z 60-1600, UV 240 nm
[0055] When the laminated nonwoven fabric 10 is a component of an absorbent article such as a sanitary product or a disposable diaper for children or adults, the adhesive used to join the laminated nonwoven fabric 10 to other components in the absorbent article is melted and softened by heating with a heating means such as a dryer, and then the laminated nonwoven fabric 10 is peeled off and removed.
[0056] The treatment agent containing compound A and compound B is applied to the constituent fibers of the second fiber layer 12, so that compound A and compound B can be disposed in the second fiber layer 12. As a method for attaching the treatment agent to the surface of the constituent fibers (application method), various known methods can be adopted without particular limitation. For example, application by spray, application by slot coater, application by roll transfer, immersion in the treatment agent, etc. can be mentioned. These treatments may be performed on the fibers before they are made into a web, or may be performed after the fibers are made into a web by various methods. By applying the treatment agent containing compound A and compound B to the constituent fibers of the second fiber layer 12, the constituent fibers are hydrophilized. The adhesion amount (adhesion rate) of compound A and compound B in the laminated nonwoven fabric 10 may be adjusted by the composition of the treatment agent containing compound A and compound B and the application amount of the treatment agent.
[0057] The treatment agent may contain components other than compound A and compound B. That is, the second fiber layer 12 may contain other compounds in addition to compound A and compound B. In this case, the other compounds may also be present in a state of being attached to the surfaces of the fibers constituting the second fiber layer 12. The other compounds will be described in detail below. In the following description, the content ratios and contents (adhesion rates) of compound A, compound B, and other compounds in the second fiber layer 12 may be adjusted by the compositions of compound A, compound B, and other compounds in the treatment agent, or the application amount of the treatment agent.
[0058] From the viewpoint of further improving the dryness, it is preferable that the second fiber layer 12 further contains one or both of a phosphate ester-type anionic surfactant and a silicone compound in addition to the compound A and the compound B. The phosphate ester-type anionic surfactant and the silicone compound also contribute to the antistatic property and abrasion resistance when the laminated nonwoven fabric 10 is processed.
[0059] Examples of the phosphate-type anionic surfactants that can be used include alkyl phosphate salts and alkyl ether phosphate salts. The alkyl group in the alkyl phosphate salts can be a straight-chain alkyl group having 8 to 22 carbon atoms. This alkyl group can be modified with, for example, a polyoxyalkylene group. Examples of the alkyl ether phosphate salts include polyoxyalkylene alkyl ether phosphate salts. From the viewpoint of further improving the liquid draw-in property, the alkyl phosphate ester salt or the alkyl ether phosphate ester salt is preferably an alkali metal salt or an alkaline earth metal salt, and can be selected from sodium, potassium, magnesium, calcium or ammonium, with the potassium salt being preferred. The phosphate ester type anionic surfactants mentioned above may be used alone or in combination of two or more.
[0060] Examples of silicone compounds include dimethyl silicone, polyether-modified silicone, methylphenyl silicone, alkyl-modified silicone, higher fatty acid-modified silicone, methylhydrogen silicone, fluorine-modified silicone, epoxy-modified silicone, carboxy-modified silicone, carbinol-modified silicone, and amino-modified silicone, etc. The silicone compounds may be used alone or in combination of two or more. From the viewpoint of further improving the liquid absorption, it is preferable that polyether-modified silicone is disposed as the silicone compound in the second fiber layer 12. The polyether-modified silicone is silicone modified with a polyoxyalkylene group (polyether chain). Examples of the polyoxyalkylene group include a polyoxyethylene (POE) group, a polyoxypropylene (POP) group, a polyoxybutylene (POB) group, and groups obtained by polymerizing two or more of the monomers constituting these groups.
[0061] From the same viewpoint as above, when one or more agents selected from a phosphate ester-type anionic surfactant and a silicone compound are adhered to the second fiber layer 12 in addition to compound A and compound B, the respective contents (adhesion rates) of compound A, compound B, phosphate ester-type anionic surfactant, and silicone compound in the second fiber layer 12 are preferably within the following ranges. In the second fiber layer 12, the content of the phosphate ester-type anionic surfactant relative to 100 parts by mass in total of compound A and compound B is preferably 30 parts by mass or more, more preferably 75 parts by mass or more, and preferably 900 parts by mass or less, more preferably 400 parts by mass or less, and is preferably 30 parts by mass or more and 900 parts by mass or less, more preferably 75 parts by mass or more and 400 parts by mass or less. In the second fiber layer 12, the content of the silicone compound relative to 100 parts by mass in total of compound A and compound B is preferably 30 parts by mass or more, more preferably 75 parts by mass or more, and is preferably 400 parts by mass or less, more preferably 200 parts by mass or less, and is preferably 30 parts by mass or more and 400 parts by mass or less, more preferably 75 parts by mass or more and 200 parts by mass or less. The adhesion rate of the phosphate ester-type anionic surfactant in the second fiber layer 12 is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and is preferably 2.00% by mass or less, more preferably 1.00% by mass or less, and is preferably 0.05% by mass or more and 2.00% by mass or less, more preferably 0.10% by mass or more and 1.00% by mass or less. The adhesion rate of the silicone compound in the second fiber layer 12 is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and also preferably 1.00 mass% or less, more preferably 0.50 mass% or less, and also preferably 0.05 mass% or more and 1.00 mass% or less, more preferably 0.10 mass% or more and 0.50 mass% or less.
[0062] Each of compound A, compound B, and the other compounds described above may be present throughout the entire thickness direction of the second fiber layer 12, or may be present only in a portion of the thickness direction, for example, only on the second face F2 side.
[0063] The first fiber layer 11 may also contain compounds such as compound A, compound B, and a phosphate-type anionic surfactant. In this case, each compound may be present in a state of being attached to the surface of the fibers constituting the first fiber layer 11. Each compound is disposed in the first fiber layer 11 by applying a treatment agent containing the compound to the fibers constituting the first fiber layer 11. The application method may be the method described above.
[0064] When the compound A and the compound B are also disposed in the first fiber layer 11, the adhesion rate of these compounds in the first fiber layer 11 is preferably within the following range. The adhesion rate of compound A in the first fiber layer 11, i.e., the content ratio of the mass of compound A to the total mass of the first fiber layer 11, is preferably 2.00 mass% or less, more preferably 1.00 mass% or less, and even more preferably is substantially free of compound A. The total mass of the laminated nonwoven fabric 10 includes the mass of the laminated nonwoven fabric 10 itself as well as the mass of the attached substances such as compound A and compound B. The adhesion rate of compound B in the first fiber layer 11, i.e., the mass ratio of compound B to the total mass of the first fiber layer 11, is preferably 2.00 mass% or less, more preferably 1.00 mass% or less, and even more preferably is substantially free of compound B. With respect to the content of compound A or compound B, "substantially free" means that the content is preferably less than 0.50% by mass, more preferably less than 0.10% by mass, and even more preferably less than 0.01% by mass.
[0065] The adhesion rate of the treatment agent containing compound A and compound B in the first fiber layer 11, i.e., the mass content of the treatment agent relative to the total mass of the first fiber layer 11, is preferably 0.02 mass% or more, more preferably 0.10 mass% or more, and is preferably 4.00 mass% or less, more preferably 2.00 mass% or less, preferably 0.02 mass% or more and 4.00 mass% or less, more preferably 0.10 mass% or more and 2.00 mass% or less.
[0066] From the viewpoint of further improving the liquid-drawing ability, it is preferable that one or both of the above-mentioned phosphate ester-type anionic surfactant and silicone compound are disposed in the first fiber layer 11. From the same viewpoint as above, it is preferable that the adhesion rates of the phosphate ester-type anionic surfactant and the silicone compound in the first fiber layer 11 are within the following ranges. The adhesion rate of the phosphate ester-type anionic surfactant in the first fiber layer 11 is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and is preferably 2.00 mass% or less, more preferably 1.00 mass% or less, and is preferably 0.05 mass% or more and 2.00 mass% or less, more preferably 0.10 mass% or more and 1.00 mass% or less. The adhesion rate of the silicone compound in the first fiber layer 11 is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and also preferably 2.00 mass% or less, more preferably 1.00 mass% or less, and also preferably 0.05 mass% or more and 2.00 mass% or less, more preferably 0.10 mass% or more and 1.00 mass% or less.
[0067] From the same viewpoint as above, it is preferable that the first fiber layer 11 contains either or both of a dialkylsulfonic acid and a betaine surfactant. Specific examples of dialkylsulfonic acids include dioctyl sulfosuccinic acid, didecyl sulfosuccinic acid, ditridecyl sulfosuccinic acid, etc., and these can be used alone or in combination of two or more. Examples of the betaine type surfactant include alkyl betaine type surfactants, amidopropyl betaine type surfactants, sulfobetaine type surfactants, imidozolinium betaine type surfactants, carbobetaine type surfactants, phosphate ester type amphoteric surfactants, etc., and these can be used alone or in combination of two or more. From the viewpoint of further improving the dryness of the laminated nonwoven fabric 10, it is preferable to use a carbobetaine type surfactant as the betaine type surfactant.
[0068] From the viewpoint of further improving the liquid drawability, it is preferable that the adhesion rates of the dialkylsulfonic acid and the betaine surfactant in the first fiber layer 11 are within the following ranges. The adhesion rate of dialkylsulfonic acid in the first fiber layer 11 is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and is preferably 1.00 mass% or less, more preferably 0.50 mass% or less, and is preferably 0.01 mass% or more and 1.00 mass% or less, more preferably 0.02 mass% or more and 0.50 mass% or less. The adhesion rate of the betaine surfactant in the first fiber layer 11 is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and is preferably 1.00 mass% or less, more preferably 0.50 mass% or less, and is preferably 0.01 mass% or more and 1.00 mass% or less, more preferably 0.02 mass% or more and 0.50 mass% or less.
[0069] When the above-mentioned compound is disposed in the first fiber layer 11, the content ratio or amount (adhesion rate) of the compound may be adjusted by changing the composition of other compounds in the treatment agent or the application amount of the treatment agent. Furthermore, each of the above-mentioned compounds may be present throughout the entire thickness of the first fiber layer 11, or may be present only in a portion of the thickness, for example, only on the first face F1 side.
[0070] From the viewpoint of more easily imparting a hydrophilicity gradient and further improving the liquid drawability, it is preferable that the first fiber layer 11 contains smaller amounts of compound A and compound B than the second fiber layer 12, and it is more preferable that compound A and compound B are not contained in the first fiber layer 11.
[0071] Next, a suitable method for producing the laminated nonwoven fabric 10 of the present invention will be described with reference to the embodiment shown in FIG. 1. When the first fiber layer 11 contains a non-heat-shrinkable fiber and the second fiber layer 12 contains a heat-shrinkable fiber, the laminated nonwoven fabric 10 can be produced, for example, by the following method. First, compound A and compound B are applied to the surface of the fiber that will be the constituent fiber of the second fiber layer 12. Next, a web made of the fiber and a web containing a non-heat-shrinkable fiber are laminated, and embossed to partially bond the two webs. This results in a laminate in which two webs are laminated. Next, the laminate is heat-treated. The heat treatment is set to a temperature equal to or higher than the heat-shrinkage start temperature of the heat-shrinkable fiber contained in the second fiber layer 12. A constant temperature dryer or an air-through heat treatment machine can be used for such heat treatment. This heat treatment shrinks the constituent fibers of the second fiber layer 12, causing the first fiber layer 11 located in the area surrounded by the joints 13 to protrude toward the first face F1, forming irregularities (a three-dimensional shape). In this way, a laminated nonwoven fabric 10 having irregularities on the first face F1 is obtained.
[0072] When the first fiber layer 11 contains a heat-extensible fiber and the second fiber layer 12 contains a non-heat-extensible fiber, the laminated nonwoven fabric 10 can be produced, for example, by the following method. First, compound A and compound B are applied to the surface of the non-heat-extensible fiber. Next, a web containing the non-heat-extensible fiber and a web containing a heat-extensible fiber are laminated, and the webs are embossed to partially bond the two webs. This results in a laminate in which the two webs are laminated. In the laminate, the web containing the non-heat-extensible fiber becomes the second fiber layer 12, and the web containing the heat-extensible fiber becomes the first fiber layer 11. Next, the laminate is heat-treated at a temperature equal to or higher than the thermal elongation initiation temperature of the thermally extensible fibers contained in the first fiber layer 11. A thermostatic dryer or an air-through heat treatment machine can be used for the heat treatment. This heat treatment elongates the constituent fibers of the first fiber layer 11, causing the first fiber layer 11 located in the area surrounded by the joints to protrude toward the first surface F1, forming irregularities (a three-dimensional shape). In this way, a laminated nonwoven fabric 10 having irregularities on the first surface F1 is obtained.
[0073] The laminated nonwoven fabric of the present invention is not limited to the embodiment shown in Fig. 1. Other embodiments of the laminated nonwoven fabric according to the present invention will be described below. In the following, for the embodiments shown in Figs. 2 to 7, components different from the embodiment shown in Fig. 1 will be mainly described, and similar components will be given the same reference numerals and description will be omitted. For components that are not particularly described, the description of the embodiment shown in Fig. 1 will be applied as appropriate.
[0074] In the laminated nonwoven fabric 10a shown in FIG. 2, the laminated first fiber layer 11 and second fiber layer 12 are bonded to each other at a plurality of bonding portions 13, and the first fiber layer 11 protrudes in a direction away from the second fiber layer 12 at locations other than the bonding portions 13 to form protrusions 14. This gives the protrusions 14 a hollow structure. The bonding portions 13 form recesses 15. The protrusions 14 and recesses 15 are arranged in a scattered manner in the planar direction of the laminated nonwoven fabric 10a. More specifically, the protrusions 14 and recesses 15 are formed in a dispersed state in each of two mutually orthogonal directions (the X direction and the Y direction in FIG. 2), and multiple rows of the protrusions 14 and recesses 15 are formed in each of the X direction and the Y direction, in which the protrusions 14 and the recesses 15 are alternately arranged.
[0075] The laminated nonwoven fabric 10a shown in Fig. 2 can be produced in a manner similar to that described in JP 2015-112343 A, by laminating a first fiber layer 11 that has been deformed into an uneven shape onto a second fiber layer 12, and then embossing the resulting layer to bond the two fiber layers 11, 12. The first fiber layer 11 can be deformed into an uneven shape by being fed between a first roll and a second roll whose peripheral surfaces are in an interlocking shape.
[0076] The laminated nonwoven fabric 10b shown in Figures 3(a) and (b) has an uneven shape on both the first surface F1 and the second surface F2, and the uneven shape on the first surface F1 corresponds to the uneven shape on the second surface F2. More specifically, the laminated nonwoven fabric 10b has a convex portion 14 and a concave portion 15 on the first surface F1 side, and a back side convex portion 17 and a back side concave portion 16 on the second surface F2 side. The convex portion 14 on the first surface F1 side protrudes toward the first surface F1 side and forms a space that is open toward the second surface F2 side. The concave portion 15 on the first surface F1 side protrudes toward the second surface F2 side and forms a space that is open toward the first surface F1 side. The second surface F2 side of the recess 15 on the first surface F1 side forms a back side convex portion 17 protruding toward the second surface side, and the second surface F2 side of the protrusion 14 on the first surface F1 side forms a back side recess 16 protruding toward the first surface side. As shown in FIG. 3(b), in the laminated nonwoven fabric 10b of this embodiment, the laminated first fiber layer 11 and second fiber layer 12 are integrated to form the unevenness on the first surface F1 and the unevenness on the second surface F2.
[0077] The laminated nonwoven fabric 10b shown in Figures 3(a) and (b) can be manufactured by a method similar to that described in JP 2013-124428 A. Specifically, a web containing thermally adhesive fibers that will become the first fiber layer 11 is placed on a support having an uneven shape and air permeability, and hot air (hereinafter also referred to as "first hot air") is blown onto the web from the opposite side of the support to shape the web along the uneven shape of the support. Next, a second hot air having a higher temperature than the first hot air is blown onto the shaped web on the support to fuse the fibers of the web together, thereby fixing the shaped shape and manufacturing the first fiber layer 11 having an uneven shape. Next, a web that will become the second fiber layer 12 containing heat-fusible fibers is laminated on the first fiber layer 11, and hot air is blown onto the web to heat-fusibly bond the fibers of the web to each other while conforming to the uneven shape of the first fiber layer 11, thereby producing a laminated nonwoven fabric 10b in which the first fiber layer 11 and the second fiber layer 12 are bonded together.
[0078] The laminated nonwoven fabric 10c shown in Fig. 4 has a ridge-furrow shape on the first surface F1 side. More specifically, the laminated nonwoven fabric 10c has a convex ridge portion 14a and a concave ridge portion 15a that is thinner than the convex ridge portion 14a. The convex ridge portion 14a and the concave ridge portion 15a each extend in one direction (Y direction in Fig. 4), and the convex ridge portions 14a and the concave ridge portions 15a are alternately arranged in a direction perpendicular to the extending direction (X direction in Fig. 4). The convex ridge portions 14a are convex portions and the concave ridge portions 15a are concave portions, so that the laminated nonwoven fabric 10c has an uneven shape on the first surface F1 side, while the second surface F2 side is flat.
[0079] The laminated nonwoven fabric 10d shown in Figures 5(a) and (b) has a ridge-furrow shape on both the first surface F1 and the second surface F2, and the ridge-furrow shape on the first surface F1 corresponds to the ridge-furrow shape on the second surface F2. More specifically, the laminated nonwoven fabric 10d has a convex streak portion 14a and a concave streak portion 15a on the first surface F1 side, and a back side convex streak portion 17a and a back side concave streak portion 16a on the second surface F2 side. The convex streak portion 14a on the first surface F1 side protrudes toward the first surface F1 side and forms a space that is open toward the second surface F2 side. The concave streak portion 15a on the first surface F1 side protrudes toward the second surface F2 side and forms a space that is open toward the first surface F1 side. The second surface F2 side of the concave streak portion 15a on the first surface F1 side forms a back side convex streak portion 17a protruding toward the second surface side, and the second surface F2 side of the convex streak portion 14a on the first surface F1 side forms a back side concave streak portion 16a protruding toward the first surface side. The convex streak portion 14a and the concave streak portion 15a, as well as the back side convex streak portion 17a and the back side concave streak portion 16a, each extend in one direction (Y direction in FIG. 5(a)). On the first surface F1 side, the convex streak portions 14a and the concave streak portions 15a are alternately arranged in a direction perpendicular to the extending direction of the convex streak portions 14a and the concave streak portions 15a (X direction in FIG. 5(a)). Similarly, on the second surface F2 side, the back side convex streak portions 17a and the back side concave streak portions 16a are alternately arranged in a direction perpendicular to the extending direction of the back side convex streak portions 17a and the back side concave streak portions 16a (X direction in FIG. 5(a)). As shown in FIG. 5(b), in the laminated nonwoven fabric 10d of this embodiment, the laminated first fiber layer 11 and second fiber layer 12 are integrated to form a ridge-and-furrow shape on the first surface F1 and a ridge-and-furrow shape on the second surface F2.
[0080] 6(a) and 6(b), the laminated nonwoven fabric 10e has, on the first surface F1 side, a plurality of protruding portions 14 and linear recessed portions 15 surrounding the protruding portions 14. The recessed portions 15 are arranged in a lattice pattern, and protruding portions 14 are formed in each of the regions partitioned by the lattice-shaped recessed portions 15. 6(b) shows an enlarged cross-sectional view of a protrusion 14 in the laminated nonwoven fabric 10e of this embodiment. In this embodiment, the interior of the protrusion 14 has a solid structure filled with the constituent fibers of the first fiber layer 11 and the second fiber layer 12, and the first fiber layer 11 mainly protrudes toward the first face F1. In addition, the recess 15 includes a joint portion where the constituent fibers of the first fiber layer 11 and the second fiber layer 12 are consolidated and joined.
[0081] 7(a) and (b) shows a laminated nonwoven fabric 10f having a plurality of protruding portions 14 and a plurality of recessed portions 15 on the first surface F1 side, and the protruding portions 14 are arranged in a staggered pattern. The protruding portions 14 have a substantially circular shape, and the apex thereof is located at the center of the protruding portions 14 in a plan view. The protruding portions 14 have a hollow structure in which a hollow space is formed between the first fiber layer 11 and the second fiber layer 12 (see FIG. 7(b)).
[0082] The laminated nonwoven fabric 10 of the present invention can be preferably used as a component of an absorbent article. An absorbent article generally includes an absorbent body that absorbs and retains bodily fluids, a top sheet that is disposed on the skin-facing side of the absorbent body and can come into contact with the wearer's skin, and a back sheet that is disposed on the non-skin-facing side of the absorbent body. The absorbent article preferably includes the above-mentioned laminated nonwoven fabric 10 as a top sheet. With such a configuration, the residual body fluid such as menstrual blood on the top sheet is suppressed, and excellent dryness is obtained. From the viewpoint of more reliably achieving such dryness, it is preferable that the laminated nonwoven fabric 10 in the absorbent article is arranged so that the surface on the first fiber layer 11 side faces the skin.
[0083] The "skin-facing surface" is the surface of the absorbent article or its constituent member (e.g., absorbent body) that faces the wearer's skin when the absorbent article is worn. The "non-skin-facing surface" is the surface of the absorbent article or its constituent member that faces the opposite side to the skin when the absorbent article is worn. In other words, the skin-facing surface is the surface that is relatively close to the wearer's skin, and the non-skin-facing surface is the surface that is relatively far from the wearer's skin. "When worn" and "worn state" refer to the normal proper wearing position, i.e., the state in which the absorbent article is worn while maintaining the proper wearing position.
[0084] The present invention is not limited to the above-described embodiment and can be modified as appropriate. For example, in the above-described embodiment, the laminated nonwoven fabric 10 has a two-layer structure consisting of the first fiber layer 11 and the second fiber layer 12, but it may have a laminated structure of three or more layers. In this case, it is preferable to have another layer between the first fiber layer 11 and the second fiber layer 12 from the viewpoint of further improving the liquid absorption ability.
[0085] In relation to the above-mentioned embodiments, the present invention further discloses the following laminated nonwoven fabric and an absorbent article including the same. <1> A laminated nonwoven fabric having at least two layers, a first fiber layer and a second fiber layer laminated thereon, the second fiber layer has a bulk density higher than that of the first fiber layer; A laminated nonwoven fabric, in which the following compound A and compound B are disposed in the second fiber layer: Compound A: Hydroxyalkanesulfonic acid salt having 12 to 22 carbon atoms Compound B: Internal olefin sulfonate having 12 to 22 carbon atoms
[0086] <2> The second fiber layer further includes one or both of a phosphate ester type anionic surfactant and a silicone compound. <1> The laminated nonwoven fabric according to claim 1. <3> The compound A contains a compound represented by the following formula (1): <1> or <2> The laminated nonwoven fabric according to claim 1. [ka] In the formula, X represents H, Na, K, Mg, Ca, or ammonium. R1 and R2 each independently represent an alkyl group, and the total number of carbon atoms of both is 10 or more and 20 or less. <4> In the second fiber layer, one or both of the following compounds A1 and A2 are disposed as the compound A. <1> ~ <3> 13. The laminated nonwoven fabric according to claim 12 . Compound A1: Hydroxyalkanesulfonate having 16 carbon atoms Compound A2: Hydroxyalkanesulfonate having 18 carbon atoms <5> the second fiber layer contains both the compound A1 and the compound A2, and the ratio of the content of the compound A1 to the content of the compound A2 in the second fiber layer (A1:A2) is 2:1 to 1:2, preferably 3:2 to 2:3; <4> The laminated nonwoven fabric according to claim 1. <6> The compound B contains a compound represented by the following formula (2): <1> ~ <5> 13. The laminated nonwoven fabric according to claim 12 . [ka] In the formula, X represents H, Na, K, Mg, Ca, or ammonium. R3 and R4 each independently represent an alkyl group, and the total number of carbon atoms of both is 9 to 19. <7> In the second fiber layer, one or both of the following compounds B1 and B2 are disposed as the compound B. <1> ~ <6> 13. The laminated nonwoven fabric according to claim 12 . Compound B1: Internal olefin sulfonate having 16 carbon atoms Compound B2: Internal olefin sulfonate having 18 carbon atoms <8> The second fiber layer contains both the compound B1 and the compound B2, and the ratio of the content of the compound B1 to the content of the compound B2 in the second fiber layer (B1:B2) is 2:1 to 1:2, preferably 3:2 to 2:3. <7> The laminated nonwoven fabric according to claim 1. <9> The mass ratio (A / B) of the compound A to the compound B in the second fiber layer is 2.0 or more and 12.0 or less, preferably 3.0 or more, more preferably 3.5 or more, even more preferably 4.0 or more, and preferably 10.0 or less, more preferably 8.0 or less, even more preferably 7.0 or less, and preferably 3.0 or more and 10.0 or less, more preferably 3.5 or more and 8.0 or less, even more preferably 4.0 or more and 7.0 or less. <1> ~ <8> 13. The laminated nonwoven fabric according to claim 12 . <10> The adhesion rate of the treatment agent containing the compound A and the compound B in the second fiber layer is 0.05% by mass or more, preferably 0.10% by mass or more, and 10.00% by mass or less, preferably 4.00% by mass or less, and is 0.05% by mass or more and 10.00% by mass or less, preferably 0.10% by mass or more and 4.00% by mass or less. <1> ~ <9> 13. The laminated nonwoven fabric according to claim 12 .
[0087] <11> a phosphate ester type anionic surfactant is disposed in the second fiber layer; The adhesion rate of the phosphate ester type anionic surfactant in the second fiber layer is 0.05% by mass or more, preferably 0.10% by mass or more, and 2.00% by mass or less, preferably 1.00% by mass or less, and is 0.05% by mass or more and 2.00% by mass or less, preferably 0.10% by mass or more and 1.00% by mass or less. <1> ~ <9> 13. The laminated nonwoven fabric according to claim 12 . <12> a silicone compound is disposed in the second fiber layer; The adhesion rate of the silicone compound in the second fiber layer is 0.05% by mass or more, preferably 0.10% by mass or more, and 1.00% by mass or less, preferably 0.50% by mass or less, and is 0.05% by mass or more and 1.00% by mass or less, preferably 0.10% by mass or more and 0.50% by mass or less. <1> ~ <11> 13. The laminated nonwoven fabric according to claim 12 . <13> The first fiber layer contains a smaller amount of the compound A and the compound B than the second fiber layer, or the compound A and the compound B are not contained in the first fiber layer. <1> ~ <12> 13. The laminated nonwoven fabric according to claim 12 . <14> The adhesion rate of the compound A in the first fiber layer is 2.00% by mass or less, preferably 1.00% by mass or less, and more preferably substantially free of the compound A. <13> The laminated nonwoven fabric according to claim 1. <15> a phosphate ester-type anionic surfactant is disposed in the first fiber layer; The adhesion rate of the phosphate ester type anionic surfactant in the first fiber layer is 0.05% by mass or more, preferably 0.10% by mass or more, and 2.00% by mass or less, preferably 0.50% by mass or less, and is 0.05% by mass or more and 2.00% by mass or less, preferably 0.10% by mass or more and 0.50% by mass or less. <1> ~ <14> 13. The laminated nonwoven fabric according to claim 12 . <16> a silicone compound is disposed in the first fiber layer; The adhesion rate of the silicone compound in the first fiber layer is 0.05% by mass or more, preferably 0.10% by mass or more, and 2.00% by mass or less, preferably 0.50% by mass or less, and is 0.05% by mass or more and 2.00% by mass or less, preferably 0.10% by mass or more and 0.50% by mass or less. <1> ~ <15> 13. The laminated nonwoven fabric according to claim 12 . <17> The first fiber layer is provided with either or both of a dialkylsulfonic acid and a betaine type surfactant. <1> ~ <16> 13. The laminated nonwoven fabric according to claim 12 . <18> The ratio of the bulk density of the first fiber layer to the bulk density of the second fiber layer (bulk density of the first fiber layer / bulk density of the second fiber layer) is 0.30 or more and 0.90 or less, preferably 0.40 or more and 0.80 or less. <1> ~ <17> 13. The laminated nonwoven fabric according to claim 12 . <19> The second fiber layer has a smaller fiber fineness than the first fiber layer. <1> ~ <18> 13. The laminated nonwoven fabric according to claim 12 . <20> The ratio of the fineness of the constituent fibers of the first fiber layer to the fineness of the constituent fibers of the second fiber layer (fineness of the constituent fibers of the first fiber layer / fineness of the constituent fibers of the second fiber layer) is 1.01 or more and 8.00 or less, preferably 1.03 or more and 5.00 or less. <19> The laminated nonwoven fabric according to claim 1.
[0088] <21> The basis weight of the laminated nonwoven fabric 10 is 10 g / m 2 More than 20 g / m 2 More than 120g / m 2 Less than 100 g / m 2 and 10 g / m 2 More than 120g / m 2 Less than 20 g / m 2 More than 100g / m 2 The above-mentioned <1> ~ <20> 13. The laminated nonwoven fabric according to claim 12 . <22> The first fiber layer has a basis weight of 5 g / m 2 More than 10 g / m 2 More than 60g / m 2 Less than 50 g / m 2 and 5 g / m 2 More than 60g / m 2 Less than 10 g / m 2 More than 50g / m 2 The above-mentioned <1> ~ <21> 13. The laminated nonwoven fabric according to claim 12 . <23> The second fiber layer has a basis weight of 5 g / m 2 More than 10 g / m2 More than 60g / m 2 Less than 50 g / m 2 and 5 g / m 2 More than 60g / m 2 Less than 10 g / m 2 More than 50g / m 2 The above-mentioned <1> ~ <22> 13. The laminated nonwoven fabric according to claim 12 . <24> The second fiber layer includes helically crimped fibers. <1> ~ <23> 13. The laminated nonwoven fabric according to claim 12 . <25> the first fibrous layer contains heat extensible fibers and the second fibrous layer contains non-heat extensible fibers; <1> ~ <23> 13. The laminated nonwoven fabric according to claim 12 . <26> The sheet has a first surface formed by the first fiber layer, and a second surface located on the opposite side to the first surface, and has a plurality of protrusions protruding toward the first surface. <1> ~ <25> 13. The laminated nonwoven fabric according to claim 12 . <27> the first fibrous layer and the second fibrous layer have a plurality of integral joints; <1> ~ <26> 13. The laminated nonwoven fabric according to claim 12 . <28> The above <1> ~ <27> An absorbent article comprising the laminated nonwoven fabric according to any one of the above. <29> The device includes an absorbent body and a top sheet disposed on the skin-facing side of the absorbent body, The top sheet includes the laminated nonwoven fabric, and is arranged so that the surface of the first fiber layer faces the skin. <28> An absorbent article as described above. EXAMPLES
[0089] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass". It should be noted that Examples 1 and 2 are reference examples.
[0090] (i) Preparation of Compound A2 and Compound B2 A treatment agent to be applied to the constituent fibers of the laminated nonwoven fabric 10 was produced by the following method: 7000 g (25.9 mol) of 1-octadecanol (product name: Kalcol 8098, derived from palm kernel oil, manufactured by Kao Corporation) and 700 g (10% by mass based on the raw material alcohol) of γ-alumina (manufactured by STREM Chemicals) as a solid acid catalyst were charged into a flask equipped with a stirrer, and a reaction was carried out for 10 hours at 280° C. while circulating nitrogen through the system (nitrogen flow rate: 7000 mL / min) under stirring to produce a raw material internal olefin of C18. Next, the C18 raw material internal olefin was sulfonated with SO3 gas in a thin film flow-down type sulfonation device, and after 1 minute, it was neutralized and hydrolyzed with KOH to obtain a crude sulfonate composition. This crude sulfonate composition was washed and purified with petroleum ether to obtain a sulfonate composition. The content of compound A2 (C18 hydroxyalkanesulfonate) in the obtained sulfonate composition was 84.0 parts by mass, and the content of compound B2 (C18 internal olefin sulfonate) was 16.0 parts by mass. The content of the C18 raw material internal olefin could not be detected by gas chromatography under the above analysis conditions. An example of such compound A2 is shown in the following formula (3).
[0091] [ka]
[0092] (ii) Preparation of Compound A1 and Compound B1 Using 1-hexadecanol (product name: "Kalcol 6098", derived from palm kernel oil, manufactured by Kao Corporation) as a raw material, a C16 raw material internal olefin was produced by the same method as in (i) above. The C16 raw internal olefin was sulfonated with SO3 gas in a thin film flow-down sulfonation apparatus, and after 1 minute, neutralized and hydrolyzed with KOH to obtain a crude sulfonate composition. The crude sulfonate composition was washed and purified with petroleum ether to obtain a sulfonate composition. The content of compound A1 (C16 hydroxyalkanesulfonate) in the obtained sulfonate composition was 85.0 parts by mass, and the content of compound B1 (C16 internal olefin sulfonate) was 15.0 parts by mass. The content of the C16 raw internal olefin could not be detected by gas chromatography under the above analysis conditions. An example of such compound A1 is shown in the following formula (4).
[0093] [ka]
[0094] Example 1 In Example 1, the laminated nonwoven fabric 10 shown in Fig. 1 was produced using the following fibers S1 and S2. The fiber S1 was used as a constituent fiber of the first fiber layer 11, and the fiber S2 was used as a constituent fiber of the second fiber layer 12. The fiber S1 was a non-heat-shrinkable fiber, and the fiber S2 was a heat-shrinkable fiber. Fiber S1: core-sheath type composite fiber (fineness 2.4 dtex, core polyethylene terephthalate 50% by mass / sheath polyethylene 50% by mass) Fiber S2: Potentially crimpable fiber [fineness 2.3 dtex, side-by-side type composite fiber made of 50% polypropylene (PP) and 50% linear low-density polyethylene (LLDPE), heat shrinkage starting temperature 60°C]
[0095] A treatment agent consisting of the following compound was applied to the surface of the fiber S1. Specifically, the fiber S1 was immersed in a dilute solution in which the treatment agent was dissolved in ion-exchanged water, and then dried, so that the treatment agent was applied to the surface of the fiber S1. Compound C1: Phosphate ester type anionic surfactant: potassium polyoxyethylene alkyl phosphate, manufactured by Miyoshi Oil Co., Ltd., product name "Anphorex MP-2K" Compound D1 Silicone compound: polyether modified silicone, manufactured by Shin-Etsu Chemical Co., Ltd., product name "KF-6012" Compound D2 Silicone compound: Dimethyl silicone, manufactured by Shin-Etsu Chemical Co., Ltd., product name "KM-903" Compound E1 Dialkylsulfonic acid: Dioctyl sulfosuccinic acid, manufactured by Kao Corporation, trade name "Pelex OT-P" Compound F1 Betaine type surfactant: stearyl betaine, manufactured by Kao Corporation, product name "Amphitol 86B"
[0096] The sulfonate composition (a mixture of compound A2 and compound B2) obtained in the above (i) was used as a treating agent, and the treating agent was applied to the surface of fiber S2 in the same manner as for fiber S1. The composition of the treatment agent applied to the fibers S1 and S2, and the adhesion rate (mass %) of the treatment agent relative to the mass of the fibers S1 and S2 are shown in Table 1 below.
[0097] After applying the treatment agent, a web made of fiber S1 and a web made of fiber S2 were laminated together to form a laminate in which both webs were laminated. Next, the laminate was subjected to ultrasonic embossing to partially bond both webs together at a plurality of joints 13 arranged in a scattered manner. The joints 13 were formed so that the area ratio was 12.8%. Next, hot air was passed through the laminate for 5 to 10 seconds to crimp the fiber S2 of the second fiber layer 12, shrink the second fiber layer 12, and cause the first fiber layer 11 between the joints 13 to protrude in a convex shape, forming a plurality of convex portions 14, thereby producing a laminated nonwoven fabric 10. Such a laminated nonwoven fabric 10 had an uneven structure in which the joints 13 were recessed portions 15 and the portions other than the joints 13 were convex portions 14. The bulk density of each of the first fiber layer 11 and the second fiber layer 12 in the laminated nonwoven fabric 10 was measured by the method described above. The measurement results are shown in Table 1 below.
[0098] Example 2 In Example 2, a laminated nonwoven fabric 10 was produced in the same manner as in Example 1, except that the sulfonate composition (a mixture of compound A1 and compound B1) obtained in the above (ii) was applied as a treatment agent to the fiber S2 (constituent fiber of the second fiber layer 12).
[0099] Example 3 In Example 3, the sulfonate composition obtained in (i) above (a mixture of compound A2 and compound B2) was mixed with compound C1 and compound D1 to form a treatment agent, which was applied to fiber S2 (constituent fiber of the second fiber layer 12). The composition of the treatment agent in Example 3 is shown in Table 1 below. A laminated nonwoven fabric 10 was produced in the same manner as in Example 1, except that such a treatment agent was used.
[0100] Example 4 In Example 4, the sulfonate composition obtained in (ii) above (a mixture of compound A1 and compound B1) was mixed with compound C1 and compound D1 to form a treating agent, which was applied to fiber S2 (constituent fiber of the second fiber layer 12). The composition of the treating agent in Example 4 is shown in Table 1 below. A laminated nonwoven fabric 10 was produced in the same manner as in Example 1, except that such a treating agent was used.
[0101] Example 5 In Example 5, the treatment agent applied to the fiber S2 (constituent fiber of the second fiber layer 12) in Example 4 was applied to both the fiber S1 and the fiber S2. Except for this, the laminated nonwoven fabric 10 was produced in the same manner as in Example 1.
[0102] Example 6 In Example 6, a laminated nonwoven fabric 10e shown in Figures 6(a) and 6(b) was produced using fiber S1 and the following fibers S3 and S4. Fibers S1 and S3 were used as constituent fibers of the first fiber layer 11, and fiber S4 was used as constituent fiber of the second fiber layer 12. Fiber S3: Heat-stretchable fiber (fineness 3.3 dtex, core 70% polypropylene / sheath 30% polyethylene, heat-stretching starting temperature 115°C) Fiber S4: Non-thermal extensible fiber [fineness 1.8 dtex, core polyethylene terephthalate 50% by mass / sheath polyethylene 50% by mass]
[0103] The same treatment agent as that applied to fiber S1 in Example 1 was applied to the surfaces of fiber S1 and fiber S3, respectively. The application method was the same as in Example 1. The adhesion rate of the treatment agent relative to the mass of fiber S1 was 0.48 mass%, and the adhesion rate of the treatment agent relative to the mass of fiber S3 was 0.46 mass%. Table 1 below shows the average adhesion rate of the treatment agent in these fibers S1 and S3 as the adhesion rate of the treatment agent (mass%). Moreover, the same treatment agent as that applied to the fibers S2 in Example 3 was applied to the surfaces of the fibers S4 (constituent fibers of the second fiber layer 12).
[0104] After applying the treatment agent, a web made of fiber S4 and a web made of fiber S1 and fiber S3 mixed at a ratio of 1:1 were laminated, and ultrasonic embossing was performed from the side of the blended web to form linear recesses (joints), and a laminate was formed in which both webs were partially joined at the recesses. The joints 13 were formed so that the area ratio was 9.6%. Next, the laminate was subjected to air-through processing to elongate the heat-extensible fibers present in the parts other than the recesses. As a result, the first fiber layer 11 was protruded in a convex shape to form multiple protrusions 14, and a laminated nonwoven fabric 10e was produced. In the laminated nonwoven fabric 10e, the constituent fibers of the first fiber layer 11 protruded toward the first surface F1 side to form protrusions 14 protruding toward the first surface F1 side, while the joints 13 became linear recesses 15, so that the parts other than the joints 13 became protrusions 14, resulting in an uneven structure (see FIG. 6(b)).
[0105] Example 7 In Example 7, the treatment agent applied to the fibers S2 (constituent fibers of the second fiber layer 12) in Example 4 was applied to the fibers S4. Aside from this, a laminated nonwoven fabric 10e was produced in the same manner as in Example 6.
[0106] [Comparative Examples 1 to 3] In Comparative Example 1, a laminated nonwoven fabric 10 was produced in the same manner as in Example 1, except that a treating agent consisting of compound E1 was applied to fibers S2. In Comparative Example 2, a laminated nonwoven fabric 10 was produced in the same manner as in Example 1, except that a treating agent consisting of Compound C1, Compound D1 and Compound E1 was applied to the fibers S2. In Comparative Example 3, a laminated nonwoven fabric 10e was produced in the same manner as in Example 6, except that a treating agent consisting of compound E1 was applied to fibers S4.
[0107] For the laminated nonwoven fabrics 10 obtained in Examples 1 to 5 and Comparative Examples 1 and 2, the amount of liquid wetback on the surface of the laminated nonwoven fabric 10 was evaluated by the following evaluation method 1.
[0108] <Evaluation method 1> Using a cold spray, an absorbent was removed from a sanitary napkin manufactured by Kao Corporation (product name "Lorrie Shiawase Suhada" manufactured in 2020). A laminated nonwoven fabric 10 was placed on the skin-facing surface of the absorbent, and an elliptical cylindrical liquid injection device was placed on the laminated nonwoven fabric 10 so as to be located at the center of the laminated nonwoven fabric. The laminated nonwoven fabric 10 was placed so that the second fiber layer 12 faced the absorbent, and the liquid injection device was placed on the first surface F1 (first fiber layer 11) of the laminated nonwoven fabric 10. Such a liquid injection device had an elliptical shape with a major axis of 5.5 cm and a minor axis of 3.0 cm, and the cylindrical part was used as a liquid injection hole. With the liquid injection device placed on the laminated nonwoven fabric 10, 3.0 g of defibrinated horse blood (24 cP) was injected into the cylinder. Next, after 50 seconds from the time when the horse blood is no longer in the cylinder, the injector is removed, and 10 seconds later (i.e., 1 minute after the horse blood is no longer in the injector), a tissue paper (Kleenex (registered trademark)) folded to 9.5 cm x 5.5 cm is placed on the part of the laminated nonwoven fabric 10 where the horse blood was injected, and 5 g / cm 2A weight was placed on the tissue so that a load of 100 g was applied. Five seconds later, the weight was released, and the mass (Wb) of the tissue paper was measured to determine the amount of liquid remaining on the surface of the laminated nonwoven fabric 10. Furthermore, two minutes after the weight was released, the injection of the defibrated horse blood and the subsequent operations were repeated. That is, the operation of injecting defibrated horse blood into the same laminated nonwoven fabric 10 and measuring the mass (Wb) of the tissue paper that had absorbed the defibrated horse blood remaining on the surface of the laminated nonwoven fabric 10 was performed twice. The amount of remaining liquid (mg) in the laminated nonwoven fabric 10 was calculated by subtracting the mass (Wa) of the tissue paper before it was placed on the laminated nonwoven fabric 10 from the mass (Wb) of the tissue paper that had absorbed the stripped horse blood (Wb-Wa). The above measurement was repeated three times, and the amount of remaining liquid (mg) after the second injection of stripped horse blood in each measurement (i.e., after a total of 6.0 g of stripped horse blood had been injected) was calculated, and the average of these values was calculated. The measurement results are shown in Table 1. The amount of remaining liquid in this evaluation method can be used as an index showing the extent to which the wearer's skin becomes wet due to the liquid remaining on the surface of the laminated nonwoven fabric 10. The smaller the value of the amount of remaining liquid on the surface of the laminated nonwoven fabric 10, the less liquid remains on the surface of the nonwoven fabric, which means that the nonwoven fabric has excellent dryness and feels good on the skin even after absorbing liquid.
[0109] For the laminated nonwoven fabrics 10d obtained in Examples 6 to 7 and Comparative Example 3, the amount of liquid wetback on the surface was evaluated by the following Evaluation Method 2.
[0110] <Evaluation method 2> Using a cold spray, the second sheet and absorbent were removed from a sanitary napkin manufactured by Kao Corporation (product name "Lorier Slim Guard" manufactured in 2020). The absorbent and the second sheet were removed in an integrated state. Next, the laminated nonwoven fabric 10e was placed on the skin-facing surface of the second sheet. Next, the above-mentioned liquid injection device was placed on the laminated nonwoven fabric 10e so as to be located at the center of the laminated nonwoven fabric 10e. The laminated nonwoven fabric 10e was also placed so that the second fiber layer 12 faced the absorbent, and the liquid injection device was placed on the first surface F1 (first fiber layer 11) of the laminated nonwoven fabric 10e. Next, 3.0 g of defibrinated horse blood (24 cP) was injected into the cylinder of the liquid injection device on the laminated nonwoven fabric 10e. Three minutes after the injection, 3.0 g of defibrinated horse blood (24 cP) was further injected, and 50 seconds later the injector was removed. 10 seconds later (i.e., 1 minute after the horse blood disappeared from the injector), the laminated nonwoven fabric 10e was placed on an OHP film. A tissue paper (Kleenex®) folded to 9.5 cm x 5.5 cm was placed on the laminated nonwoven fabric 10e at the site where the defibrinated horse blood was injected, and 2.5 gf / cm was applied on the tissue paper. 2 A weight was placed on the tissue so that a load of about 245 Pa was applied, and the tissue was left stationary for 3 seconds. The load was then removed, and the mass (Wb) of the tissue was measured. The amount of liquid remaining on the surface of the laminated nonwoven fabric 10e (mg) was calculated by subtracting the mass (Wa) of the tissue before being placed on the laminated nonwoven fabric 10e from the mass (Wb) of the tissue (Wb) (Wb-Wa). This measurement was repeated twice, and the average amount of liquid remaining on the surface of the laminated nonwoven fabric 10e was calculated. The measurement results are shown in Table 1. The amount of remaining liquid in this evaluation method can also be used as an index showing the degree to which the wearer's skin becomes wet due to the liquid remaining on the surface of the laminated nonwoven fabric 10e. The smaller the value of the amount of remaining liquid, the less liquid remains on the surface of the laminated nonwoven fabric 10e, which means that the fabric has excellent dryness and feels good on the skin even after absorbing the liquid.
[0111] The horse defibrinated blood used in the measurements of <Evaluation Method 1> and <Evaluation Method 2> was manufactured by Japan Bio Test Laboratory Co., Ltd. When horse defibrinated blood is left to stand, the high viscosity parts (red blood cells, etc.) settle, and the low viscosity parts (plasma) remain as the supernatant. The horse defibrinated blood was prepared by mixing the high viscosity and low viscosity parts, and the mixing ratio was adjusted so that the viscosity was 24 cP (25°C). This viscosity was assumed to be that of high viscosity menstrual blood. A TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. was used for the adjustment. The condition was 12 rpm.
[0112] [Table 1]
[0113] As is clear from the results shown in Table 1, the laminated nonwoven fabrics 10 of Examples 1 to 5, which include the laminated nonwoven fabric 10 having compound A and compound B disposed therein, had a smaller amount of liquid remaining on the surface than Comparative Example 1, and the laminated nonwoven fabrics 10d of Examples 6 and 7 had a smaller amount of liquid remaining on the surface than Comparative Example 3. That is, it was shown that in the laminated nonwoven fabrics of Examples 1 to 7, even when a highly viscous body fluid was repeatedly injected therein as in <Evaluation method 1> and <Evaluation method 2>, body fluid was less likely to remain on the surface of the nonwoven fabric. Comparison of Examples 1 to 4 shows that the combined use of a phosphate ester-type anionic surfactant and a silicone compound together with Compounds A and B is effective in suppressing the amount of residual liquid. In particular, Example 4, in which Compound A1 and Compound B1, each having 16 carbon atoms, were combined with a phosphate ester-type anionic surfactant and a silicone compound, showed a significant effect in suppressing the amount of residual liquid. Furthermore, a comparison between Examples 4 and 5 indicates that the amount of residual liquid is more effectively suppressed when the compounds A and B are not provided in the first fiber layer 11. The above results demonstrate that the laminated nonwoven fabric of the present invention effectively prevents liquid from remaining on the surface, and therefore provides good dryness. [Explanation of symbols]
[0114] 10 Laminated nonwoven fabric 11 First fiber layer 12 Second fiber layer 13 Joint 14 Convex 15 Recess
Claims
1. A laminated nonwoven fabric having at least two layers, a first fiber layer and a second fiber layer laminated thereon, the second fiber layer has a bulk density higher than that of the first fiber layer; The second fiber layer has a smaller fiber fineness than the first fiber layer, A laminated nonwoven fabric, comprising the second fiber layer and the following compound A and compound B, a phosphate-type anionic surfactant, and a silicone compound disposed therein: Compound A: Hydroxyalkanesulfonic acid salt having 12 to 22 carbon atoms Compound B: Internal olefin sulfonate having 12 to 22 carbon atoms
2. A laminated nonwoven fabric as described in claim 1, wherein the ratio of the fineness of the constituent fibers of the first fiber layer to the fineness of the constituent fibers of the second fiber layer (fineness of the constituent fibers of the first fiber layer / fineness of the constituent fibers of the second fiber layer) is 1.01 or more and 8.00 or less.
3. The laminated nonwoven fabric according to claim 1 or 2, wherein one or both of the following compounds A1 and A2 are disposed as the compound A in the second fiber layer. Compound A1: Hydroxyalkanesulfonate having 16 carbon atoms Compound A2: Hydroxyalkanesulfonate having 18 carbon atoms
4. A laminated nonwoven fabric described in any one of claims 1 to 3, wherein the first fiber layer is provided with either one or both of a dialkylsulfonic acid and a betaine type surfactant.
5. The laminated nonwoven fabric according to any one of claims 1 to 4, wherein the second fiber layer contains helically crimped fibers.
6. 6. The laminated nonwoven fabric according to claim 1, comprising a first surface formed by the first fiber layer and a second surface located opposite to the first surface, and having a plurality of convex portions protruding toward the first surface.
7. The laminated nonwoven fabric according to any one of claims 1 to 6, wherein the first fiber layer and the second fiber layer have a plurality of integrated joints.
8. An absorbent article comprising the laminated nonwoven fabric according to any one of claims 1 to 7.
9. The device includes an absorbent body and a top sheet disposed on the skin-facing side of the absorbent body, The absorbent article according to claim 8 , wherein the topsheet comprises the laminated nonwoven fabric, and the surface of the first fiber layer is disposed so as to face the skin.
Citation Information
Patent Citations
Surface sheet for absorptive article
JP2003250836A
Three-dimensional nonwoven fabric
JP2005314825A
Water permeability-imparting agent and water-permeable fiber with the same attached thereto
JP2007247128A
Absorbent article
JP2009268559A
Absorbent article
JP2016112174A